Analisis Sales Growth Pada PT XL Axiata Tbk - Nurul Hikmah; Aris Munandar (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine how much sales growth at PT XL Axiata Tbk. The research method used is descriptive research. The research instrument used was a list of tables and income statement. The population used for 13 years and the study sample for 10 years from 2009 to 2018. The sampling used is purposive sampling. By collecting data using secondary data. secondary data in the form of income statement data. the data analysis technique used is one sample t test with the results showing PT XL Axiata Tbk sales growth not greater than 10%